Flight Capital as a Portfolio Choice - Hoeffler, Anke.; Collier, Paul.; Pattillo, Catherine (Washington, D.C. : International Monetary Fund, 1999)
This paper sets flight capital in the context of portfolio choice, focusing upon the proportion of private wealth that is held abroad. There are large regional differences in this proportion, ranging from 5 percent in South Asia to 40 percent in Africa. We explain cross-country differences in portfolio choice by variables that proxy differences in the risk-adjusted rate of return on capital. We apply the results to four policy questions: how the East Asian crisis affected domestic capital outflows; herd effects; the effect of the IMF-World Bank debt relief initiative for heavily-indebted poor countries (HIPC) on capital repatriation; and why so much of Africa's private wealth is held outside the continent.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet